2012
DOI: 10.1007/s00213-012-2781-2
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of ethanol–nicotine drug mixtures in mice: dual interactive mechanisms of overshadowing and potentiation

Abstract: Rationale One possible basis for the proclivity of ethanol and nicotine co-abuse is an interaction between the discriminative stimulus (SD) effects of each drug. Objectives The current work sought to assess the discriminative control of ethanol and nicotine cues in mice trained with drug mixtures and to determine whether interactive mechanisms of overshadowing and potentiation occur. Methods Male C57BL/6J mice were trained to discriminate ethanol (1.5 g/kg) alone or ethanol plus nicotine (0.4, 0.8 or 1.2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 31 publications
(48 reference statements)
2
27
1
Order By: Relevance
“…By contrast. Ford et al (2012Ford et al ( , 2013 reported that the discriminative stimulus effects of E exceeded N; however that study was conducted with mice and required much higher doses of nicotine (0.4-1.2 mg) and ethanol (1.5 g) to show the effects. Clearly, more parametric analyses involving dose-response manipulations will explicate the relative contribution of N and E to the NE compound in future investigations using extinction training, as the lack of such evaluations was an obvious limitation of the present set of studies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…By contrast. Ford et al (2012Ford et al ( , 2013 reported that the discriminative stimulus effects of E exceeded N; however that study was conducted with mice and required much higher doses of nicotine (0.4-1.2 mg) and ethanol (1.5 g) to show the effects. Clearly, more parametric analyses involving dose-response manipulations will explicate the relative contribution of N and E to the NE compound in future investigations using extinction training, as the lack of such evaluations was an obvious limitation of the present set of studies.…”
Section: Discussionmentioning
confidence: 93%
“…Most recently. Ford, Davis, McCracken, and Grant (2013), and also see Ford, McCracken, Davis, Ryabinin, and Grant (2012), conducted systematic replications in mice but found evidence that EtOH overshadowed nicotine; the NMDA glutamate receptor was found to play a role. To date, these are the only reported studies evaluating the stimulus effects of the NE compound.…”
mentioning
confidence: 94%
“…The mice were then returned to their home cage and fed their daily food diet, and remained in the procedural room for another 55 min before being transported to a separate procedural room where they were placed in a CO2 chamber. At 90 min total after initial treatment injection mice were euthanized (Ford et al, 2012). Normally, a perfusion of paraformaldehyde (PFA) is used to preserve the tissue and organs of the mouse, but in this particular procedure PFA was not used because it can prevent the primary antibody (c-Fos) from binding properly.…”
Section: Dosing and Treatmentmentioning
confidence: 99%
“…Once the mice were trained, the mice were divided into separate groups and given an intraperitoneal (i.p.) injection of either the saline, alcohol, or nicotine-alcohol combination (Ford et al, 2012). A double-14 alternation schedule of drug administration was used where saline (i.e., non-drug) was given two days in a row and then alcohol or both drugs for two days (saline, saline, drug, drug).…”
Section: Dosing and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation